Determining the pressure shift coefficient for carbon dioxide absorption line at a specific wavelength (Damascus University Journal for the basic sciences, 2025)
In this work, the effect of pressure on the shift of the carbon dioxide absorption peak exposed to collision at a specific wavelength in the near infrared range was studied using a spectroscopic system based on direct absorption. The graphs expressing the resulting shift as a function ofpressure were drawn and the shift coefficients were extracted in three collision cases: self-collision, with nitrogen gas, and with oxygen gas. The results were within expectations and were consistent with the literature.
Keywords: Laser spectroscopy; Direct absorption; Long optical path; Absorption line; Pressure; Particle collision; Spectral line shift